NOx Emission Indices of Subsonic Long-Range Jet Aircraft at Cruise Altitude: In Situ Measurements and Predictions - Schulte, P.; Schlager, H.; Ziereis, H.; Schumann, U.; Baughcum, S.; Deidewig, F. (1997)
In the course of the Commissions of the European Communities project “Pollution From Aircraft Emissions in the North Atlantic Flight Corridor (POLINAT)”, in situ measurements of NO, NOx , and CO2 volume mixing ratios in the near-field exhaust plumes of seven subsonic long-range jet aircraft have been carried out by using the research aircraft Falcon of the Deutsche Forschungsanstalt für Luft- und Raumfahrt (DLR). For three additional aircraft, only NO and CO2 were measured. Plume ages of 50 s to 150 s have been covered, with maximum observed exhaust gas enhancements of 319 parts per billion by volume and 51 parts per million by volume for Δ[NOx] and Δ[CO2], respectively, in relation to ambient values. Aircraft cruising altitudes and Mach numbers ranged from 9.1 to 11.3 km and from 0.77 to 0.85, respectively. These measurements are used to derive NOx emission indices for seven of the individual aircraft/engine combinations. The NOx emission indices derived range from 12.3 g/kg to 30.4 g/kg. They are compared with predicted emission index values, calculated for the same aircraft engine and the actual conditions by using two newly developed fuel flow correlation methods. The calculated emission indices were mostly within or close to the error limits of the measured values. On average, the predictions from both methods were 12% lower than the measured values, with an observed maximum deviation of 25%. The ratio γ = [NO2]/[NOx] found during the present measurements ranged from 0.06 to 0.11 for five daytime cases and was around 0.22 for two nighttime cases. By use of a simple box model of the plume chemistry and dilution these data were used to estimate the initial value γ0 present at the engine exit plane. We found γ0 values between 0 and 0.15. These were applied to estimate the corresponding NO2 for the three cases in which only NO was measured.